Phytochemical Profile and Antioxidant Activity of Hydro-distillated from Gynostemma pentaphyllum Makino with Hydrogen Gas: Antioxidant activity of hydrogen-rich G. pentaphyllum Makino distillate - Kim, Min Young (Journal of Tropical Life Science, 2024)
Hydrogen-rich Gynostemma pentaphyllum Makino distillate (HRGD) is made by distilling G. pentaphyllum Makino with hydrogen gas to produce the final product. The study evaluated the total phenolic and flavonoid contents of HRGD, as well as its antioxidant properties, including scavenging activities for various radicals such as 2,2-diphenyl-1-picryl-hydrazyl (DPPH), superoxide anion (O2-), hydrogen peroxide radical (H2O2), nitric oxide radical (NO•) and 2,2´-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+), along with a ferrous ion chelating assay. Total phenolic and flavonoid contents were 42330 mg gallic acid and 36300 mg rutin equivalents/100 g, respectively. HRGD exhibited significant antioxidant and free radical scavenging activities in vitro, which were dose-dependent and superior to those of standard antioxidants. HRGD exhibited higher scavenging activities for DPPH, O2-, H2O2, NO• and ABTS•+ radicals, as well as ferrous ion chelating activity than standard antioxidants (p < 0.05). The results showed that HRGD could be an economical and readily accessible source of natural antioxidants and a possible food and pharmaceutical supplement.